CULTURAL PECULIARITIES OF DOING BUSINESS IN EUROPEAN COUNTRIES - Zelisko , Н.; Markovych , Н. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
The article studies the cultural peculiarities of doing business in European countries. The main aspects of business culture are identified. It has been determined that effective business in different countries requires a deep understanding of cultural characteristics and differences in today's globalized world. It has been found that today, despite numerous studies in the field of international business, the issue of cultural peculiarities of doing business in European countries remains relevant and insufficiently studied. Knowledge and understanding of these cultural differences are critical for entrepreneurs and managers seeking to succeed in the European market. Lack of such knowledge can lead to misunderstandings, conflicts and business failures. It is established how the cultural characteristics of different European countries affect business and what strategies can be successfully applied to adapt to these cultural differences. At the same time, the study found that business culture is constantly changing, adapting to the environment, market demands and social needs. The process of ethical decision-making depends on many factors, such as general human culture, social traditions, norms and rules of conduct, personal experience, etc. Globalisation trends, which bring a significant number of business participants to the world stage where different cultures and civilisations meet, further complicate this process. It is believed that business culture is a kind of external shell of the enterprise's operating environment, which is influenced by the national characteristics of the country and the specifics of doing business in a particular region and is complemented by the internal component - corporate and organisational culture. It is established that another important feature of European business is its progressiveness. It seems that the European market is so saturated that it is difficult for new entrepreneurs to find their place. The constant desire to expand and strengthen international cooperation makes the European market extremely dynamic.